Bigenderism at work? Organizational responses to trans men and trans women employees - Joel Rudin; Tejinder Billing; Andrea Farro; Yang Yang (Organization Management Journal (OMJ), 2020)
Purpose - This study aims to test bigenderism, a universalistic theory that purports to explain why trans men employees enjoy greater organizational acceptance and superior economic outcomes compared to trans women employees. Design/methodology/approach - Respondents were presented with one of two case studies in which they had to choose whether or not to respect the right of a trans employee to use the restroom of their choice at work. The only difference between the two case studies was the gender of the trans employee. In one case, the employee was a trans man and in the other case, the employee was a trans woman. Findings - The gender of the trans employee had no impact on the choices of the respondents. Research limitations/implications - The chief research implication is that heightened discrimination against trans men may better be explained by situational theories of transphobia rather than the universalistic theory that was tested in this paper. The primary research limitation was the use of American undergraduate business students as respondents. Practical implications - Organizations need to be especially vigilant in protecting the restroom rights of their transgender employees, which may entail eliminating gender-segregated restrooms. Originality/value - This paper is original in that it uses an experimental design to test the theory of bigenderism. It adds value by encouraging experimental research that examines situational theories of transphobia.
Keywords: 650; Transgender; Gender; Employment discrimination; Theories of discrimination; Restrooms